Investment Attractiveness of Regions: Methodic Aspects of the Definition and Classification of Impacting Factors - Mustafakulov, Sherzod (European Scientific Journal, ESJ, 2017)
The article focuses on the classification of national and regional resources defining the socio-economic capacity of territories, and it discloses its essential elements. It provides various analysis of existing conditions for maximizing the usage of regional economic capacity, i.e. the use of investment flow methods for production process, hiring labour resources, and its effective direction in the expanded reproduction of the economy. The author provides critical review of economic researches focused on national/regional economic capacity, their methods of assessment of economic capacity, and defining investment attractiveness of regions. Moreover, various factors have to be taken into account in forming regional development and investment programs. The author attempts to provide casual analysis of main macro and mezo-scale tasks to be solved by regional authorities in order to provide relatively balanced regional development and prevent sharp widening of income inequalities. Hence, the article provides scientific-methodic recommendations on priority directions for the provision of socio-economic development and for assessing the value of investment attractiveness of regions with long-term historical specialisation on agricultural production.